International Handbook of Educational Leadership and Administration
XLIV, 1176 p. 3 illus.
Keywords: EDITORS This introduction to the International Handbook of Educational Lead ership and Administration describes some of the motivation for devel oping the book and several assumptions on which is based much of the work represented in its 31 chapters. A synopsis of the contents of those chapters is also provided. SOME KEY ASSUMPTIONS It is sometimes suggested that the search for an adequate understanding of leadership is doomed to fail. After all, there is little evidence of agreement about the concept in spite of prodigious efforts dating back hundreds if not thousands of years. Such a view is captured, for exam ple, in Bennis' observation that: Of all the hazy and confounding areas in social psychology, leadership theory undoubtedly contends for top nomination. Probably more has been written and less is known about lead ership than any other topic in the behavioural sciences. (1959, page 259) We do not find this state of affairs discouraging (nor entirely accurate) and, of course, it did not prevent Bennis from proceeding either. One reason for our desire to continue in the face of such discouraging words is that a great deal of leadership research aspires to develop a general theory, a theory which applies to all or most domains of organized human activity. This aspiration inevitably produces decontextualized and, therefore, abstract categories of practice. Howard Gardner's (1995) depiction of leadership as story telling is a case in point.